High-frequency echography of the eye in macular hole diagnosis - T. N. Kiseleva; K. V. Lugovkina; A. N. Bedretdinov; P. A. Bychkov; M. V. Ryabina; M. S. Zaytsev (Российский офтальмологический журнал)
Purpose: a comparative estimation of ultrasound examinations of the posterior eye pole of patients with a macular hole using a long-focus high-frequency (20 MHz) and a standard 10 MHz probe with optical coherence tomography (OCT).Materials and methods. 20 patients with a macular hole in at least one eye were examined using OCT of the macular area and B-mode echography with a standard 10 MHz probe and a long-focus high-frequency 20 MHz probe.Results. The complex OCT/ ultrasound examination detected a macular hole in 22 (100 %) eyes, while OCT alone confirmed the diagnosis in 20 eyes (91 %). OCT could not be performed in 2 eyes due to a dense cataract. Ultrasound examination with a 20-MHz probe detected a macular hole in 16 eyes (73 %), whilst the standard ultrasound method (10 MHz probe) could only detect it in 10 eyes (45 %).Conclusion. High-frequency ultrasound examination of the eye can be used for screening aimed at detecting a possible macular hole in cases of opacities of the optical media of the eye.